IMPLEMENTASI PENDIDIKAN KARAKTER DI SMP NEGERI 1 TELUK GELAM DALAM MENGATASI SIKAP PRIMODIALISME - Agustina, Evi; Tobari, Tobari (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
Indonesia is currently in a multidimensional crisis, the moral shift of teenagers is very significant, if it is not immediately anticipated, it will have an impact on the destruction of a State. In order to overcome it, itÂ  is very necessary that the values of the characters are implemented on learners early, so that they have a life prinsiple in building and continuing the journey of this country. One of the most credible concepts of education as a solution of primodialism is character education. SMP Negeri 1 Teluk Gelam has conducted character education to minimize the perimodialism attitude. Because the generation that is prepared now is a generation that will continue the establishment of the Unitary Republic of Indonesia. The research used qualitative research method of ethnography by describing character education conducted at SMP Negeri 1 Teluk Gelam namely (1) Aperception which is associated with religious values by every subject teacher 5 minutes before learning begins; (2) Applying discipline; (3) Implementation; (4) Habituation activities; (5) cooperation with Tanjung Lubuk Polsekta in guiding the students; (6) Active communication with parents.